Analysis of Land Disputes Arising from Land Procurement Activities in the Development of Public Facilities And Infrastructure (Review of Law Number 2 of 2012 concerning Land Acquisition) - Ryan Rainhard Marchello; Evita Isretno Israhadi; Suparno Suparno (Publikasiku, 2023)
Land as a living space with all the people has a social function that must be able to maintain a balance between individual interests, social interests, and the interests of the state. Infrastructure development in the frame of public interest is closely related to land as the medium. So that land and development activities are a unit that cannot be separated from each other. The consequences of this have implications for the existence of land procurement for the public interest (land procurement for public interest) in realizing the welfare of the lives of its citizens who are just and prosperous equally as the goal of being an Indonesian state as stated in the fourth paragraph of the 1945 Constitution of the Republic of Indonesia. The study shows the implementation of land acquisition that is not by applicable legal procedures, the occurrence of maladministration and implementation errors such as lack of socialization, not involving all land rights holders, and there is no dialogue process between the parties before determining the location of the development, compensation that does not accommodate all non-physical needs of society. This error caused a dispute in the infrastructure development process because it was not by the mandate of Law Number 12 of 2012 concerning Land Procurement for Development in the Public Interest.